Aqueous seeded RAFT polymerization for the preparation of self-assemblies containing nucleobase analogues - Abad, Miriam; Nardi, Martina; Oriol, Luis; Piñol, Milagros; Blasco, Eva (Polymer chemistry, 2023)
Self-assemblies containing the nucleobase analogue 2,6-diacylaminopyridine (DAP) have been successfully prepared for the first time by aqueous seeded RAFT polymerization in high concentrations. For this purpose, a diblock copolymer containing poly(ethylene glycol) (PEG) and DAP polymethacrylate blocks was used as a macro-chain-transfer agent (PEG124-b-PDAP9-CTA) for the polymerization of 2-hydroxypropyl methacrylate (HPMA) in water. From the systematic variation of the degree of polymerization and solid concentration, a phase diagram has been generated that correlates both variables with the morphologies of this new system. Self-assemblies have been characterized by TEM and DLS, observing morphologies from low to high order (from spherical micelles to worms and to vesicles). Self-assembly morphologies are stable for almost a year, except in the case of worms that turn into spherical micelles after a few weeks. In addition, H-bonding supramolecular functionalization of the DAP repeating units during aqueous seeded RAFT polymerization has been examined by functionalization with a cross-linker with four thymine groups. Finally, the loading and the subsequent release of Nile Red have been proven in both supramolecular cross-linked and non-cross-linked self-assemblies.
Online veröffentlicht: 22. November 2022
Gesehen am 09.03.2023